Clinically localised prostate cancer is microsatellite stable. - Azzouzi, A; Catto, J; Rehman, I; Larre, S; Roupret, M; Feeley, K; Cussenot, O; Meuth, M; Hamdy, F (2007)
OBJECTIVES: To determine the frequency of microsatellite instability (MSI) change with mono-, di- and tetranucleotide markers in clinically localized prostate cancer, and to correlate those markers with clinical and pathological variables. MATERIALS AND METHODS: Two forms of MSI have been described in human cancer: MSI typical of hereditary nonpolyposis colon cancer, defined with mono- and dinucleotide repeat MS; and a second variety of MSI is best seen at selective tetranucleotide repeats, i.e. elevated microsatellite alterations at select tetranucleotides (EMAST). Prostate specimens were taken from 50 patients. The MS analysis used the Bethesda consensus panel (BCP) and four tetranucleotide loci shown to detect the presence of EMAST. RESULTS: All but four tumours were stable for the 14 loci investigated. There were two (4%) cases with adenomatous polyposis coli (APC) instability among the BCP markers and the same instability rate (4%) amongst the EMAST markers. These four tumours were all unstable at one locus of the 10 markers of the BCP that classified them as MS stable. CONCLUSIONS: The MSI related to a mismatch repair deficiency or to the EMAST does not seem to be important in prostate cancer in the early stages of the disease.